Performing Under Uncertainty: Contextualized Engagement in Wildland Firefighting. (4th March 2015) - Barton, Michelle A.; Sutcliffe, Kathleen M.; Vogus, Timothy J.; DeWitt, Theodore
<x xml:space="preserve">Abstract</x> In this paper, we propose that performance under uncertainty and ambiguity is enabled by a two‐pronged set of practices enacted by leaders and frontline workers. These contextualized practices fuel performance by enabling teams and organizations to both discern, interpret and make sense of important discrepancies as situations unfold (what we refer to as anomalizing), and to develop a richer understanding of a situation (what we call proactive leader sensemaking). Together, these situation‐specific practices contextualize engagement and promote capabilities to contingently tailor actions to unfolding conditions. We test our hypotheses using data gathered from a sample of wildland firefighters and find strong support for our theorizing. We also identify a set of additional group and situational conditions that provide a more nuanced understanding of factors that contribute to reliable performance under dynamic uncertainty. Together, the findings provide quantitative evidence for the micro‐foundations of effective performance in uncertain contexts.